Molecular epidemiology and immunopathogenesis of bovine viral diarrhea virus: a growing threat to regional cattle industry of Xinjiang, China - Gao, Jindong; Kuang, Lei; Yin, Jinhua; Zhang, Mengdi; Kulyar, Md. F.; Hu, Changmin (Frontiers in Microbiology, 2025)
Bovine viral diarrheal virus (BVDV), identified as a serious global pathogen, presents a significant and formidable challenge for the global cattle sector. This presents not only serious economic consequences but also serious immunopathological consequences causing lasting impacts. In the Chinese province of Xinjiang, where the ruminants are high and the topographical features unique and contribute towards complex epidemiology, multiple genotypes of the BVDV are continuously interacting and adapting. This includes the persistent presence of the earlier predominant BVDV1, the rising trend towards the antigenically complex BVDV2, and the recent presence of the HoBi-like (BVDV3) strain, contributing toward complexity. The purpose of this review is to present a detailed analysis relative to the molecular epidemiology, genomic diversity levels, and complex pathology associated with the persistence and spreading of the infection by the BVDV. In light of the country’s inability to execute the efficacious eradication of the infection, stringent biosafety measures need to be adopted, the genomic investigation has to be increased, and the establishment of the multi-valent vaccine for the induction of the local strain of the infection should be encouraged. These steps need to be taken towards the rising danger of the presence of the BVDV, not only towards the province but also towards the larger territories beyond.